Double Burden of Malnutrition among Women of Reproductive Age and Its Associated Factors in Makassar District - Fachruddin, Ismi Irfiyanti; Pratiwi, Hardyanti (Media Gizi Indonesia, 2024)
The double burden of malnutrition, especially on women, continues to increase, including in Makassar City, Indonesia. The prevalence of malnutrition is quite high based on BMI category in the adult female population aged >18 years in Makassar City, namely thin (8.64%), fat (14.33%), and obese (29.75%). This study aims to compare factors related to undernutrition and overnutrition status in women of childbearing age (WUS) in Makassar District. This research is a cross-sectional study of suburban women aged 16–44 years at the Bara-baraya Community Health Center, Makassar District using a quota sampling technique for two months. Anthropometric measurements were carried out to determine nutritional status, calorie and protein intake were measured using a 24-hour recall questionnaire, and a structured questionnaire to determine the characteristics of respondents. The statistical test used is the Chi Square test. The prevalence of undernutrition, normal and overnutrition in the WUS group was 8.3%, 46.9% and 44.8%, respectively. There is a significant relationship between energy intake (p=0.032), dietary diversity (p=0.025), nutritional knowledge (p=0.029), and education (p=0.009) with nutritional status in women of childbearing age. No significant relationship was found between protein intake, occupation, economic status and age with nutritional status among women of reproductive age (p>0.05).